Quarantine interception of carinoclytus beetles (Cerambycidae) on teak logs (Tectona grandis) imported from Benin - Ahamed, S N; Singh, S Jasvir; Arya, Sanjay; Mathuram, Petzy C (Indian Journal of Plant Protection, 2020)
Short communication